Model Pengambilan Keputusan Garbage Can dan Dana Talangan Haji - Adiakarti Farid, Muhammad Rifa’at (Kopertais Wilayah I DKI Jakarta dan Banten, 2019)
Hajj Bailout Funds is a consumpetive financing aimed at customers to fulfill the initial deposit costs of the Hajj Implementation Costs (BPIH) determined by the Indonesian Ministry of Religion through the Integrated Hajj Computerized System (SISKOHAT), to obtain the seat number for the pilgrimage using the Qard contract and Ijarah. The Government's basis for issuing financing products for the Hajj Bailout Fund is based on the fatwa of the National Sharia Council (DSN) MUI No.29 / DSN-MUI / VI / 2002 dated June 26, 2002 concerning Financing of Hajj Arrangements by LKS (Islamic Financial Institutions). This study found that the garbage can method used only solves various problems that are on the surface, not solving a variety of other more complex problems. Among them is the problem of the pilgrimage interest which is increasing every year not accompanied by the improvement of Hajj supporting facilities; lodging, catering, passport and visa management which are often hampered by poor bureaucracy, separation of operators and regulators in carrying out hajj and the like. Overall the process of organizing the pilgrimage from year to year increasingly shows significant changes.